2017
DOI: 10.1080/09546634.2017.1341610
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on topical cetirizine in the therapeutic management of androgenetic alopecia

Abstract: Our results have shown that topical cetirizine 1% is responsible for a significant improvement of the initial framework of AGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 10 publications
4
50
1
1
Order By: Relevance
“…Prostaglandin F 2 alpha analogues such as latanoprost can increase pigmentation, thickness, length, and number of eyelashes . Prostaglandins are involved in hair growth regulation; PGE 2 and PGF 2 alpha stimulate hair growth, whereas PGD 2 has an inhibitory effect . Is has been suggested that a balance between PGE 2 and PGD 2 controls hair growth in mouse and human skin, whereas drugs that stimulate hair growth may exert their effects by acting on prostaglandin pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin F 2 alpha analogues such as latanoprost can increase pigmentation, thickness, length, and number of eyelashes . Prostaglandins are involved in hair growth regulation; PGE 2 and PGF 2 alpha stimulate hair growth, whereas PGD 2 has an inhibitory effect . Is has been suggested that a balance between PGE 2 and PGD 2 controls hair growth in mouse and human skin, whereas drugs that stimulate hair growth may exert their effects by acting on prostaglandin pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Is has been suggested that a balance between PGE 2 and PGD 2 controls hair growth in mouse and human skin, whereas drugs that stimulate hair growth may exert their effects by acting on prostaglandin pathways. It has been suggested that minoxidil increases production of PGE 2 , and topical cetirizine, which has been reported to be beneficial in androgenetic alopecia, decreases inflammatory cell infiltrate and PGD 2 production . Prostaglandins may have an action on hair growth regulation through their vasomotor effects in the dermis, inducing blood flow in the perifollicular vessels, and by inducing DNA replication and stimulation of cell division and growth …”
Section: Discussionmentioning
confidence: 99%
“…The authors recruited 85 patients (male and female patients), of which 67 were used topical cetirizine, while 18 were control patients. In this regard, Rossi et al (2017) stated that inhibition of PGD2 (as di-hydroxytestosterone) through the use of cetirizine is a further pathogenic clue in AGA, resulting to be a new and promising target treatment for AGA (Rossi et al, 2017). In this regard, Rossi et al (2017) stated that inhibition of PGD2 (as di-hydroxytestosterone) through the use of cetirizine is a further pathogenic clue in AGA, resulting to be a new and promising target treatment for AGA (Rossi et al, 2017).…”
mentioning
confidence: 99%
“…Recently, Rossi et al (2017) provided a preliminary study on the therapeutic efficacy of topical cetirizine 1% lotion applied once a day on the scalp, in management of AGA. The authors recruited 85 patients (male and female patients), of which 67 were used topical cetirizine, while 18 were control patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation